A simple and efficient off-optical axis electro-optic voltage sensor - Garcia, Marlon Rodrigues [UNESP]; Galeti, Jose Henrique [UNESP]; Higuti, Ricardo Tokio [UNESP]; Kitano, Claudio [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2014)
Sinusoidal high-voltage measurements at 50/60 Hz are very important since, at present, power delivery systems use this kind of low frequency waveforms. It is well known that conventional instrument transformers, based on electromagnetic principles, present problems with respect to their responses in the presence of harmonic distortion. On the other hand, optical instrument transformers have excellent frequency response, which significantly contributes to a more accurate measurement of these harmonic components. The high voltages of power delivery systems require monitoring by techniques that provide electrical isolation. For these reasons, optical techniques are a good choice for this application. The basic principle of remote measurement of high voltages using the Pockels effect is inspired by the principle of conventional electro-optic modulator used in optical communication systems, whose carrier works up to MHz frequencies. A typical arrangement of a bulk-type optical voltage sensor consists of an electro-optic crystal placed between two crossed polarizers. The system must usually be biased with a fixed retardation π/2 rad to the 50% transmission curve point, which can be achieved using a quarter wave-plate, avoiding the need for a high voltage bias. However, the further elimination of the quarter wave-plate from the voltage sensor would be very effective for simplifying the sensing system, improving the temperature stability and achieving the insensitivity to light wavelength. This effect can be easily achieved by a slight misalignment of the light beam propagating on the X-Z plane, through a small angle from the Z axis of the crystal. The design methodology, the theoretical projection of the electro-optic voltage sensor performance, and finally, laboratory low voltage testing are reported in this paper.